Lokalne instytucje pomocy społecznej w procesie aktywizacji społeczno-zawodowej bezrobotnych kobiet - Książkiewicz, Izabela (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
Contemporary theories of politics, and social assistance – stress that the effectiveness of social programs in the field of community work with groups at risk of marginalization processes is determined by quality of service provided in this area at the level of local institutions. The financial crisis of the welfare state – has highlighted the weakness of the central management of social programs, at the level of individual regions, and thus the need for a new approach to the problems of the excluded. Long-term unemployment, disability, many children and sex are those factors that promote the processes of exclusion – in Poland, a group particularly at risk are women who live outside large cities. The analysis shows that the appropriate support by local aid institutions – raises the prospect of becoming independent women still excluded from the labor market. However, in order to be successful, must be complied with certain conditions into account the local conditions of socio-economic potential. A chance for the preparation of programs targeted to a specific group, including its characteristics and needs – are carried out from 2008 projects under the Human Capital Operational Programme, funded by the European Union. In this elaboration I present the experience of three municipalities voivodeship with the implementation of programs for the group of unemployed women.